Co‐occurrence of eosinophilic esophagitis and potential/probable celiac disease in an adult cohort: a possible association with implications for clinical practice. Issue 8 (6th November 2015) - Johnson, J. B.; Boynton, K. K.; Peterson, K. A.
Summary: We describe an adult cohort with eosinophilic esophagitis (EoE) and evidence of celiac disease (CD), propose a change in diagnostic practice to better characterize these conditions, and hypothesize new directions for research. Pediatric studies postulate association between gluten sensitivity and EoE. However, few publications describe the prevalence, detection, or therapeutic and pathophysiologic implications of such association in adults. Retrospective chart review was done on patients diagnosed with EoE from 2009 to 2010 at University of Utah Hospitals and Clinics. Data included sex, age, presentation, duodenal pathology, tissue transglutaminase immunoglobulin A antibody (TTG) positivity, human leukocyte antigen (HLA) type (when indicated), and gross and microscopic Esophagogastroduodenoscopy (EGD) findings. Duodenal biopsy, TTG results, and HLA type were correlated. Endoscopy was repeated after gluten‐free diet. Forty‐four of 75 patients were followed in EoE specialty clinic with duodenal biopsy and TTG testing per protocol. Six EoE patients had potential or probable CD. No sex or age differences were noted between those with findings of CD and EoE and those with EoE alone. Six patients with findings of CD and EoE followed gluten‐free diet. Five underwent repeat endoscopy. Three had resolution of esophageal eosinophilia. Potential or probable CD was commonly found in adults with EoE. Diagnosis of CD may be challenging due to nonspecific symptoms and insufficient duodenal biopsy and serologic testing. Furthermore, gluten‐free diet resolved EoE findings in some patients, suggesting possible shared pathophysiology in some cases of EoE and CD. TTG testing and adequate duodenal biopsy may further direct clinical care for EoE patients, and studies are needed to elucidate mechanisms linking EoE and CD.